2022
DOI: 10.3390/nu14030559
|View full text |Cite
|
Sign up to set email alerts
|

Elovl2-Ablation Leads to Mitochondrial Membrane Fatty Acid Remodeling and Reduced Efficiency in Mouse Liver Mitochondria

Abstract: The fatty acid elongase elongation of very long-chain fatty acids protein 2 (ELOVL2) controls the elongation of polyunsaturated fatty acids (PUFA) producing precursors for omega-3, docosahexaenoic acid (DHA), and omega-6, docosapentaenoic acid (DPAn6) in vivo. Expectedly, Elovl2-ablation drastically reduced the DHA and DPAn6 in liver mitochondrial membranes. Unexpectedly, however, total PUFAs levels decreased further than could be explained by Elovl2 ablation. The lipid peroxidation process was not involved in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Our study thus confirms the role of the VLCFA elongation cycle in mitochondrial homeostasis [ 22 , 35 ]. More precisely, mitochondrial dysfunction in Hacd2 -KO embryos, and in the kidney and liver of Hacd2 -KD pups, affected both the respiratory chain complexes and respiratory coupling.…”
Section: Discussionsupporting
confidence: 87%
“…Our study thus confirms the role of the VLCFA elongation cycle in mitochondrial homeostasis [ 22 , 35 ]. More precisely, mitochondrial dysfunction in Hacd2 -KO embryos, and in the kidney and liver of Hacd2 -KD pups, affected both the respiratory chain complexes and respiratory coupling.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, alterations involving the LC-PUFA synthesis pathway causes an imbalance in the n-3/n-6 ratio and lipid peroxidation, which also leads to the production of ROS, subsequently damaging cellular functions [ 37 ]. Previous studies have found that abnormal expression of ELOVL2 and FADS2 in liver may lead to membrane fatty acid remodeling and impaired membrane lipid homeostasis [ 38 ]. In this result, the mRNA expression levels of ELOVL2 , FADS2 , ACOT7 , CYP2C , CYP4A , PTGS1 , ALOX5 , and GGT5 , which are involved in EPA and AA metabolism, were also altered in the livers of IUGR piglets.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of Elovl2 reduces lifespan and induces an accelerated aging phenotype in mice characterized by early hair loss as well as impairments in bone density, endurance, muscle strength, learning, and memory ( Li et al., 2022 ). Separate work has shown that the ablation of Elovl2 drives mitochondrial dysfunction in the mouse liver ( Gomez Rodriguez et al., 2022 ). Given that the hypermethylation of this gene is tethered to a reduced expression level with age ( Chen et al., 2020 ; Li et al., 2022 ), it is feasible that the methylation of ELOVL2 contributes to age-related pathology.…”
Section: Discussionmentioning
confidence: 99%